Discovery and Development of Anti-inflammatory Agents from Natural Products - Brahmachari, Goutam (Elsevier, 2019)
Discovery and Development of Anti-inflammatory Agents from Natural Products, the latest volume in the Natural Product Drug Discovery series, presents cutting-edge research advances in the field of bioactive natural products and natural drug formulations, with this volume focusing on molecules of natural origin and their synthetic analogues that have the potential to act against the pathogens responsible for inflammatory diseases. All aspects of each are covered, including isolations and structure elucidations, in vitro and in vivo biological activity, synthetic optimization, investigations of pharmacodynamics and kinetics, and the structure-activity relationships of anti-inflammatory natural products. Written by active researchers and leading experts, this book brings together an overview of current discoveries and trends in this field. It will be a valuable resource for researchers working to discover promising leads for the development of pharmaceuticals in the prevention and treatment of anti-inflammatory diseases.